Pengembangan Media Kartu Kuartet ASEAN pada Muatan Pembelajaran IPS - M.Y. Santi Mariani; Esti Setiawati (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to explain the steps in preparing the design of the quartet card learning media device for social studies learning material for the ASEAN region to improve the learning outcomes of sixth grade elementary school students. The type of research is R&D (Research & Development) with five steps of ADDIE model adoption. The resulting product is a multidisciplinary social studies learning media in the form of an ASEAN quartet card. The subjects in this study were 117 elementary school grade VI students from five elementary schools. The research instrument is a questionnaire and a test of student learning outcomes. Analysis of the data by means of analyzing the level of product validity and testing the gave effectiveness of using the product to improve learning outcomes. Data analysis used qualitative and quantitative analysis.The results of the validity test of the ASEAN quartet card learning media meet the very valid criteria according to material experts with a score of 98%, media experts 98% and learning experts 94%. This indicates that the learning media The ASEAN quartet card that was applied an increase in student learning outcomes and was declared effective in the ASEAN Social Studies lesson content in grade VI Elementary School.